Efficiency Analysis of Drip Irrigation and Crop Water Requirement of Watermelon (Citrullus vulgaris S.) on Ultisol Soil - Ira Septiana Pasaribu; Sumono Sumono; Saipul Bahri Daulay; Edi Susanto (Jurnal Rekayasa Pangan dan Pertanian, 2013)
This research was held to analysis the efficiency of drip irrigation and crop water requirement of watermelon on ultisol soil. The parameters observed were water discharge, crop water requirement, physical properties of the soil, and the efficiency of drip irrigation (water usage and water storage). The results of this experiment indicated that the average value of water discharge was 898.4 ml.hour-1. The highest crop water requirement in the middle phase of growth was 6.23 mm.day-1 and the lowest crop water requirement occurred in the early phase of growth was 2.80 mm.day-1. Ultisol soil has sandy clay loam texture with a bulk density of 1.18 gr.cm-3, 2.12 gr.cm-3 particle density, and porosity of 43.20%. The largest water consumption efficiency was 100% and the lowest water consumption efficiency was occurred in the middle phase of growth i.e 96.7%. The largest water storage efficiency was occurred in the middle phase i.e 89.13% and the lowest water storage efficiency was occurred at the early phase of growth i.e 33.12%. Key words: Crop Water Requirement, Efficiency, Drip Irrigation, Ultisol Soil, Watermelon